The Event of Hypertension Based on Salt, Fruit and Vegetable Consumption Habits in The Coastal Area of Belawan Sicanang - Ikhwan Ikhwan; Mutiara Husna Sari Dewi; Ryzka Aini Hutabarat; Selia Puspita Sindi Anisyah Caniago; Yulia Afnasari Siregar; Yulia Khairina Ashar (International Archives of Medical Sciences and Public Health, 2022)
The habit of consuming processed seafood which contains much sodium, is one of the risk factors for hypertension in coastal areas. High sodium levels in the blood will disrupt the fluid balance, so the heart will continue to pump vigorously, which causes an increase in blood pressure. This study aimed to determine the incidence of hypertension based on the level of salt, fruit and vegetable consumption in the coastal area of Belawan Sicanang. This study is a rapid survey research with univariate analysis conducted in 20 Belawan Sicanang Village, Medan Belawan Medan City, in October 2021. The sample of this study was 210 local people with a history of hypertension and aged 17 years. Data was collected by distributing questionnaires adopted from household questionnaires and basic health research questionnaires in 2018. Based on the results of the study, the majority of hypertension sufferers (18.5%) were in the neighbourhood of 19, female (63.0%), aged 42- 46 years old (33.3%), high school education (77.8%) and working as a housewife (35.2%). The average consumption of salt per day exceeds the optimal dose (2.57 teaspoons/day), with the average consumption of vegetables (1.48 servings/day) and fruit (0.78 servings/day) still low. Salt consumption in the community is still relatively high, and consumption of vegetables and fruit is still relatively low.